In vitro assessment of dietary mealworm (Tenebrio molitor L.) combined with a natural source of tannins (Acacia farnesiana L.) for sheep feeding - Manuel Gonzalez-Ronquillo; Navid Ghavipanje; Lizbeth E. Robles Jimenez; Eduardo Cardoso-Gutiérrez; José Manuel Pino Moreno; Manuela Renna; Einar Vargas-Bello-Pérez (Heliyon)
Recently, insects have received increased attention as feed sources for sustainable animal production. Yellow mealworm (Tenebrio molitor, TM) represents one of the most promising insect species to be used for such a purpose. Although rapid development of the use of insects as feed is expected, TM remains underutilized in ruminant nutrition. The use of natural tannin sources provides a promising prospect to improve the digestibility of insect protein sources. Hence, the present study determined the in vitro rumen fermentation patterns, dry matter disappearance (DMd) and total gas production of full-fat TM larvae meal and a natural source of tannins (Acacia farnesiana pods, AF) when combined at different inclusion levels [TM:AF equal to 0:100, 20:80, 40:60, 60:40, 80:20, and 100:0, on a dry matter (DM) basis] to form six different diets. Three Suffolk–Texel ewes [79.9 ± 10.12 kg body weight; mean ± standard deviation] with a rumen fistula were used as rumen fluid donors. Four incubation runs were carried out. The obtained data were statistically analyzed in a completely randomized design. Our results showed that 24-h gas production was enhanced with increasing inclusion levels of AF (p < 0.0001). The highest DMd (p < 0.0001) and microbial biomass production (p < 0.0001) were observed when incubating the 60TM:40AF diet. Increasing dietary TM levels were associated with an increase (p = 0.001) in N-NH3 concentrations, and a reduction (p = 0.001) in CH4 production. Overall, the best TM:AF mixture in terms of rumen gas kinetics and fermentation profile was the 60TM:40AF mixture. Further in vitro and in vivo trials should be conducted to explore the potentially desirable effects of tannins on the digestibility of TM protein and methane emissions mitigation.